Bionatura - Centro Ecuatoriano de Biotecnología y Ambiente; Universidad Católica de Oriente; Universidad Nacional Autónoma de Honduras (Centro Ecuatoriano de Biotecnología y Ambiente, 2015)
"Latin American journal of biotechnology and life sciences."
Keywords: Biotechnology : Periodicals; Biotechnology; Biotechnology; Biotechnologie : Périodiques; Latin America : Biotechnology : Periodicals; Latin America; Spain; Latin America; Amérique latine : Biotechnologie : Périodiques